Analysis of Growth of Broiler Chicken Farming Business in Hoder Village, Waigete District - Maria Inviolata Lipat; Mohamad Amir; Nur Chotimah (Jipmor: Jurnal Ilmu Pendidikan Dan Humaniora, 2024)
Determination of the sample in this study was carried out using qualitative method, and the respondents in this study were broiler chickin breeders in Hoder Village, Waigete District, and the number of respondents was 6 people. The data analysis used in this research is a SWOT analysis. The results of this study indicate the risks faced in the slag business broiler chickens in Hoder Village, Waigete District, are divided into two rinko namely production risks in the form of disease and weather, aswell as marketing risks in the form of unsanitary chickens, the number of competitors and price fluctuations. While the identification of internal and eksternal factors in the broiler breeder endang can be seen that, 1) the strengthsof the broiler breeder endang are quality products, good road access, availability of land, labor 2) Weak nesses of the broiler breeder business are the close location with settlements,water is not smooth 3) Opportunities owendby broiler chicken, waste is processed into chicken coops 4) Threats for broiler chicken breeders are the number of competitors, the presence of broiler chicken diseases strategy for developing posong chicken breeders in Villages Hoder, Waigete District, yaina improving the skills of breeders, keeping the waste from disturbing the surrounding endangy, preparing water containers, to maintain the quality of broiler chickens.